Trading old errors for new errors? The impact of electronic voting technology on party label votes in Brazil. (September 2016) - Zucco, Cesar; Nicolau, Jairo M.
Abstract: In the mid-1990s, Brazil introduced electronic voting technology that reduced residual ballots and consequently expanded de facto enfranchisement. We employ a regression discontinuity design similar to that of previous studies of the Brazilian electronic voting technology to show that electronic technology also caused a sharp rise in party label votes ( votos de legenda ) that can only be explained by voting error. We show that this error offsets a large portion of the gains in enfranchisement, highlighting the fact that even generally positive changes in voting procedures can have negative effects. Our results also suggest that party label votes should not be considered a measure of party strength in the Brazilian context. Highlights: Electronic voting technology used in Brazil generated a sharp increase in party label votes (PLV). The excess PLVs are a product of a new error, induced by the voting system. Voting system imposes a counter-intuitive order of voting and makes it easy to confuse the different elections of the day. Voters think they are voting for president first, and end up casting a PLV in congressional elections. The new error offsets a substantial portion, but not all, of the enfranchisement gains with electronic technology.